Facile removal of rhodamine B and metronidazole with mesoporous biochar prepared from palm tree biomass: adsorption studies, reusability, and mechanisms - Luqmon Azeez; Oyinlola Adefunke; Abdulrasaq O. Oyedeji; Babatunde K. Agbaogun; Hassan K. Busari; Ayoade L. Adejumo; Wasiu B. Agbaje; Adebayo E. Adeleke; Awolola O. Samuel (Water Practice and Technology, 2024)
Biochar was produced by pyrolysing palm tree bark biomass at 500 °C for the removal of rhodamine B (RhB) and metronidazole (MET). Fourier-transform infrared spectroscopy (FTIR), Brunauer–Emmett–Teller, X-ray diffraction (XRD), scanning electron microscopy, and energy-dispersive X-ray analyses were used to characterize the biochar. The biochar obtained was crystalline, mesoporous (SBET: 189.157 m2 g−1; pore diameter: 2.207 nm), clustered with prominent O–H and C = O functional groups. The pHpzc of the biochar was 7.98, and it adsorbed RhB and MET maximally at pH 3.4 and 7.2, respectively. The Langmuir and Freundlich isotherms described RhB and MET adsorption, respectively, with maximum adsorption capacities (qmax) of 31.81–224.30 mg/g for RhB and 95.44–26.76 mg/g for MET from 303 to 313 K. Both adsorbates exhibit favourable physisorption processes with pseudo-second-order kinetics, as the most appropriate. The thermodynamic parameter (−ΔG°) demonstrates spontaneous adsorption processes for RhB and MET, with spontaneity increasing with temperature for RhB and decreasing with increasing temperature for MET. The adsorption process was endothermic (+ΔH°) for RhB and exothermic (−ΔH°) for MET. Given its reusability of 96 and 95% for RhB and MET, respectively, mesoporous biochar derived from palm trees is a more promising adsorbent. HIGHLIGHTS Biochar was prepared from palm tree biomass and characterized to be mesoporous and crystalline.; Adsorption of rhodamine B and metronidazole followed Langmuir and Freundlich isotherms, respectively.; Adsorption capacities increased from 31.81 to 224.30 mg/g for RhB and decreased from 95.44 to 26.76 mg/g for MET with temperature.; The kinetics of both adsorption processes followed pseudo-second order.; Adsorption was spontaneous.;